2021
DOI: 10.3390/ani11092532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Restrictions in Portugal: A Questionnaire to Municipal and Animal Association Shelters

Abstract: The COVID-19 pandemic has an indirect impact on the health and welfare of animals. The aim of this work was to investigate the effect of COVID-19 on Municipal and Association animal shelters. A questionnaire was sent to 97 Municipal shelters and 65 Associations. Questions focused on public funding, management and animal welfare during COVID-19 restrictions. The response rate was 43.3% (42/97) for Municipal shelters and 38.5% (25/65) for Associations. Municipal shelters (67%) received over 80% of public funding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Shelters felt that they inhabited a ‘grey area’ when seeking to operate under the restrictions imposed during lockdown. This is in accordance with the findings of Gomes-Neves et al ( 2021 ) who revealed that Portuguese municipal shelters were most affected by the lack of instructions. Along with the lack of help with funding, the struggle to follow local restrictions perpetuated the feeling of being ignored and underappreciated by the authorities and the Government.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Shelters felt that they inhabited a ‘grey area’ when seeking to operate under the restrictions imposed during lockdown. This is in accordance with the findings of Gomes-Neves et al ( 2021 ) who revealed that Portuguese municipal shelters were most affected by the lack of instructions. Along with the lack of help with funding, the struggle to follow local restrictions perpetuated the feeling of being ignored and underappreciated by the authorities and the Government.…”
Section: Discussionsupporting
confidence: 93%
“…This variation is also found in other recent studies on the subject (e.g. Morgan et al 2020;Baptista et al 2021;Gomes-Neves et al 2021;Powell et al 2021).…”
Section: Promoting Co-operation and Change Within The Sectorsupporting
confidence: 86%
See 3 more Smart Citations